(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The rapid expansion of social media platforms has significantly transformed patterns of language use and challenged traditional language norms across diverse linguistic communities. This study examines the impact of social media on contemporary English language norms, focusing on changes in vocabulary, grammar, spelling, discourse practices, and pragmatic conventions. Social media environments such as microblogging platforms, social networking sites, and multimedia-sharing applications encourage speed, brevity, creativity, and informality, which collectively influence how language is produced, perceived, and evaluated. The research adopts an interdisciplinary perspective that integrates sociolinguistics, discourse analysis, and digital communication studies to explore how online interaction reshapes linguistic behavior among users, particularly students and young adults in academic contexts. Special attention is given to the tension between prescriptive norms traditionally upheld in formal education and the descriptive realities of language use in digital spaces. The study also considers the role of emojis, abbreviations, hashtags, memes, and code-switching as semiotic and linguistic resources that expand expressive possibilities while simultaneously raising concerns about standardization and linguistic accuracy. Empirical data are drawn from a corpus of social media texts, surveys of university students, and interviews with English language instructors, allowing for a comprehensive analysis of both usage patterns and attitudes toward emerging norms. The findings suggest that social media does not simply degrade language, as is often claimed in public discourse, but rather accelerates natural processes of linguistic change and diversification. At the same time, the study highlights pedagogical challenges faced by philological education in balancing respect for standard language norms with the need to acknowledge and critically engage with digital language practices. The results contribute to a more nuanced understanding of language evolution in the digital age and offer implications for language teaching, assessment, and policy in higher education contexts.